Demosthenes, "Second Philippic": Critical Edition - Hernández Muñoz, Felipe G. (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
We present a critical edition of Demosthenes’ Second Philippic. It belongs to a larger project, namely a bilingual edition of the Four Philippics. As main novelty we offer for the fi rst time the testimony of all Greek manuscripts preserved in Spain, as well as a collatio of other recentiores and both Aldine editions.